2017
DOI: 10.21649/akemu.v23i1.1511
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Learning Styles of Medical and Physiotherapy Students

Abstract: <p><strong>Background:</strong><strong>  </strong>Learning styles are the ways students learn, intake and process new information. The contribution of learning styles for educational quality is evident and have important implications to develop effective curricula. Teachers can effectively plan instructional activities if they know the learning styles of students. This study was conducted to find out the preferred learning styles of medical and physiotherapy students.<strong>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Similarly, another study has reported the highest mean score (4.08±0.5) of all the three components of the SDLRS followed by selfcontrol (3.9±0.9) [25]. Another study showed that the majority of students had a high level of readiness toward SDL; the mean score of selfcontrol was higher than self-management and desire for learning [26].…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, another study has reported the highest mean score (4.08±0.5) of all the three components of the SDLRS followed by selfcontrol (3.9±0.9) [25]. Another study showed that the majority of students had a high level of readiness toward SDL; the mean score of selfcontrol was higher than self-management and desire for learning [26].…”
Section: Discussionmentioning
confidence: 83%
“…(Rahila Nizami et al, 2017) 34 statistical significance, methods and limitations were not properly reported leading to low quality of reporting statistical significance, methods and limitations were not properly reported leading to low quality of reporting…”
Section: Discussionmentioning
confidence: 99%
“…Based on these two dimensions, four learning styles are identified: (1) an accommodator-learning through a concrete experience and active experimentation, (2) a diverger-learning through a concrete experience and reflective observation, (3) an assimilator-learning through an abstract conceptualization and reflective observation, and (4) a converger-learning through an abstract conceptualization and active experimentation [66]. Honey and Mumford's learning style theory presents an adapted version of Kolb's model, and classifies individual learning styles depending on their preference for learning from experience (an activist), reflective observation, description of processes and understanding of meaning (a reflector), observing and understanding facts and information and their relations as well as understanding of logic (a theorist), or doing and trying practical things (a pragmatist) [14,74].…”
Section: Learning Styles and Preferred Teaching Methodsmentioning
confidence: 99%
“…In order to determine student's preferred manner of obtaining new information, which enables the typification of respondent's learning styles, Honey and Mumford's [83] 80-point extensive Learning Style Questionnaire (LSQ) was used. LSQ, which classifies learners into four major groups-activists, reflectors, theorists, and pragmatists, was used as it is considered to be more suitable inventory for a business community [84], and as it is extensively employed in management training [14] and scientific research in the field [67,74]. Cronbach's alphas exhibited the reliability of both the whole instrument (α = 0.658) and individual learning style scales (α activist = 0.725; α reflector = 0.655; α theorist = 0.659; α pragmatist = 0.562).…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation